The natural infection rates of vaccine-preventable diseases among children: A literature review - Sri Yuliani Frisilia Dewi; Misnaniarti Misnaniarti; Rizma Adlia Syakurah; Najmah Najmah; Nur Alam Fajar (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Indonesia currently faces a triple burden of various disease problems, outbreaks of infectious diseases, and an increase in long-standing infectious diseases, new infectious diseases, and non-communicable diseases (NCDs). A report released in 2020 by the United Nations International Children's Emergency Fund (UNICEF) and the World Health Organization (WHO) indicated that during the Covid-19 pandemic, the postponement of routine vaccinations resulted in approximately 80 million children aged less than or equal to 12 months being susceptible to diphtheria, measles, and polio.Purpose: To review previous research in analyzing the relationship between incomplete basic vaccination and the occurrence of vaccine-preventable disease (VPD) cases.Method: This study employed a literature review design, conducting a systematic review by selecting relevant articles pertaining to the research objective. The literature study selection process was adapted from the Preferred Reporting Items for Systematic Reviews (PRISMA-ScR). Inclusion criteria for this research encompassed originality, usage of both English and Indonesian languages, keywords covering basic vaccination, adverse events following vaccination, Integrated Healthcare Centervisits, education, and the role of Integrated Healthcare Centercadres.Results: Generally, community knowledge, attitudes, family support, and the role of cadres correlated with vaccination coverage achievement. However, some studies indicated no correlation between specific variables and the infants' basic vaccination status. To enhance vaccination coverage and client satisfaction, improving community knowledge, attitudes, family support, the role of healthcare workers and Integrated Healthcare Centercadres, as well as increasing vaccine availability and vaccination guidelines, are necessary.Conclusion: To improve vaccination coverage and client satisfaction, enhancements in community knowledge, attitudes, family support, the role of healthcare workers and Integrated Healthcare Centercadres, alongside increased vaccine availability and vaccination guidelines, are essential.Suggestion: It is advisable for the community to enhance knowledge, attitudes, and support for vaccination, especially among mothers and families. The active involvement of cadres in vaccination programs and public dialogue regarding the moral ethics of vaccination also need improvement.